'I Did Not Wash My Hand for Days': The Stuplime Return of Revolutionary Speech in the Republic of Guinea. Issue 2 (1st September 2021) - McGovern, Mike
Abstract: This article focuses on the reception of revolutionary oratory in what was once known as The People's Revolutionary Republic of Guinea. Sékou Touré, Guinea's first president, captivated the nation with fiery, unscripted speeches lasting four, five, or six hours. Guinean audiences were enthralled by his sublime revolutionary rhetoric. In a 2008 coup, Captain Moussa Dadis Camara declared himself president, attempting to recreate the fervour of Guinea's revolutionary days. Guinean citizens initially provided a willing revolutionary audience, though Camara's oratory fell far short of Touré's example. The article explores how the effects of shock and boredom that Ngai describes as 'stuplimity' (2005) emerged in reaction to Camara's performances. Stuplimity was a halfway point between Guineans' initial 'revolutionary' suspension of disbelief regarding the junta's intentions and their subsequent rejection and anger, which led to the junta's collapse less than a year after it took power.